2015
DOI: 10.3389/fmicb.2015.00059
|View full text |Cite
|
Sign up to set email alerts
|

Biosurfactant production by Bacillus subtilis using corn steep liquor as culture medium

Abstract: In this work, biosurfactant production by Bacillus subtilis #573 was evaluated using corn steep liquor (CSL) as culture medium. The best results were obtained in a culture medium consisting of 10% (v/v) of CSL, with a biosurfactant production of about 1.3 g/l. To the best of our knowledge, this is the first report describing biosurfactant production by B. subtilis using CSL as culture medium. Subsequently, the effect of different metals (iron, manganese, and magnesium) on biosurfactant production was evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
89
0
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(100 citation statements)
references
References 33 publications
5
89
0
6
Order By: Relevance
“…Vazet al[46]and Ghojavand et al[47] reported surface tensions reductions to 29 mN/m and 27 mN/m respectively.For the B. subtillis CN2, the highest amount of biosurfactant produced was7150 mg L −1 of culture medium obtained when using glycerol as the carbon source at concentration of 6% (w/v). Gudiña et al[48] reported about 1300 mg L −1 of biosurfactant production by Bacillus subtilis #573 strain using corn steep liquor (CSL) culture medium consisting of 10% (v/v) of CSL. Lin et al[49] and Rahman et…”
mentioning
confidence: 99%
“…Vazet al[46]and Ghojavand et al[47] reported surface tensions reductions to 29 mN/m and 27 mN/m respectively.For the B. subtillis CN2, the highest amount of biosurfactant produced was7150 mg L −1 of culture medium obtained when using glycerol as the carbon source at concentration of 6% (w/v). Gudiña et al[48] reported about 1300 mg L −1 of biosurfactant production by Bacillus subtilis #573 strain using corn steep liquor (CSL) culture medium consisting of 10% (v/v) of CSL. Lin et al[49] and Rahman et…”
mentioning
confidence: 99%
“…[73,77,78] However, subsequent studies indicated that LP production was suitable using a number of different complex media as well as industrial wastes. These included King's B medium [50] Landy's medium, [82] corn steep liquor, [83] and glycerol waste from biodiesel production. [27,74] Optimal medium and cultivation conditions should be selected for each individual LP/BS producer to reach maximum productivity, although amounts of LP sufficient for analyses (Figure 1) can also be obtained from non-optimized cultures.…”
Section: Cultivation Of Microbes For the Production Of Lpmentioning
confidence: 99%
“…Biosurfactants are surface-active compounds synthesized by a wide range of microorganisms [13]. They are amphiphilic molecules containing hydrophobic and hydrophilic moieties and tend to interact with surfaces of different polarities and reduce the surface and interfacial tensions of solutions [5].…”
Section: Introductionmentioning
confidence: 99%